Relationship between upper limb injuries and hip range of motion and strength in high school baseball pitchers. (26th March 2021) - Hamano, Noritaka; Shitara, Hitoshi; Tajika, Tsuyoshi; Ichinose, Tsuyoshi; Sasaki, Tsuyoshi; Kuboi, Takuro; Shimoyama, Daisuke; Kamiyama, Masataka; Miyamoto, Ryosuke; Endo, Fumitaka; Nakase, Kurumi; Kobayashi, Tsutomu; et al.
We aimed to examine the relationship between hip range of motion (ROM) and abduction strength and throwing-related shoulder/elbow injuries in high school baseball pitchers. The study included 135 baseball pitchers. We asked them to fill out a questionnaire at the checkups, that included the dominant arm and the years of baseball experience. To avoid a confirmation bias, the examiners were blinded to the participants' hand dominance. All players underwent physical function measurements, such as height, weight, shoulder and hip strength, and shoulder and hip ROM. Shoulder and elbow injury was defined as shoulder and elbow pain that the patient had been aware of in the past 3 years. The results of injured and non-injured pitchers were compared. Eighty-five pitchers had experienced a shoulder or elbow injury in the past 3 years. The shoulder ROM and strength in the injured and non-injured groups did not differ to a statistically significant extent. The hip external rotation ROM on the dominant side, the hip abduction strength on the non-dominant side, and the hip abduction strength on the dominant side were significantly lower in the injured group than in the non-injured group. The results may contribute to reducing the incidence of these injuries.